A Review of Journal Clubs in Postgraduate Medical Education - Alguire, Patrick C (Blackwell Science Inc, 1998)
OBJECTIVE: To review the goals, organization, and teaching methods of journal clubs, summarize elements of successful clubs, and evaluate their effect on reading habits, and effectiveness in meeting teaching goals. Examples of clubs that utilize principles of adult learning are reviewed. DATA SOURCES: English language articles identified through a MEDLINE search (1966–1997) using the MeSH terms “internship” and “residency,” and text words “journal club” and “critical appraisal.” STUDY SELECTION: Articles on learning goals and organization were included if they represented national or regional surveys with a response rate of 65% or greater. Articles that evaluated teaching effectiveness were included if they used a controlled, educational design, or if they exemplified important adult learning principles. DATA EXTRACTION: Data were manually extracted from selected studies and reviews. DATA SYNTHESIS: A major goal for most clubs is to teach critical appraisal skills. Clubs with high attendance and longevity are characterized by mandatory attendance, availability of food, and perceived importance by the program director. Residents who are taught critical appraisal report paying more attention to the methods and are more skeptical of the conclusions, and have increased knowledge of clinical epidemiology and biostatistics, but studies have failed to demonstrate that these residents read more, or read more critically. Reading guidelines may be useful for teaching critical appraisal skills, and may be associated with increased resident satisfaction. CONCLUSIONS: Journal club formats are educationally diverse, can incorporate adult learning principles, and are an adaptable format for teaching the “new basic sciences.”